A comparative study of combined treatment with fractional carbon dioxide and targeted ultraviolet B phototherapy for facial vitiligo. Issue 7 (September 2016) - Kanokrungsee, Silada; Chanprapaph, Kumutnart; Chaiyabutr, Chayada; Vachiramon, Vasanop
Abstract Facial vitiligo is associated with considerable psychological impact. The management is challenging and requires multidisciplinary treatment. Adding fractional carbon dioxide (CO2 ) to the conventional treatment has been reported as an effective modality. This study aimed to evaluate the efficacy of combined fractional CO2 laser, targeted ultraviolet B (UVB) phototherapy, and topical steroid on facial vitiligo. A prospective, randomized, split face study was conducted on 14 patients with symmetrical non-segmental facial vitiligo. Ten sessions of fractional CO2 laser was performed on the lesions on one side of face with 2-week interval. Immediately after laser, the lesions on both side of face were treated with 10 sessions of 2-week interval targeted UVB phototherapy and twice daily application of topical 0.05 % clobetasol propionate cream. The patients were followed up for 12 weeks after the last treatment. Clinical improvement was graded by blinded dermatologists and patients using a quartile grading scale. Twelve out of 14 patients completed the study. The degree of improvement was not different between both sides in nine patients. One patient showed more improvement on the combined laser side, and two patients showed inferior results on the combined laser side. Two patients with lesser improvement on the laser-treated side had positive Koebner phenomenon on the non-facial area. The combined treatment with laser, targeted UVB, and topical steroids are not superior to targeted UVB and topical steroids in facial vitiligo. Furthermore, laser may retard the response to the standard treatment in patients with Koebner phenomenon on non-treated areas.